Enhanced nonsynaptic epileptiform activity in the dentate gyrus after kainate-induced status epilepticus. (10th September 2015) - Nogueira, G.S.; Santos, L.E.C.; Rodrigues, A.M.; Scorza, C.A.; Scorza, F.A.; Cavalheiro, E.A.; de Almeida, A.-C.G.
Highlights: NEA enhancement in the dentate gyrus is associated with increased neuronal NKCC1. NEA suppression in CA1 is related to severe neuronal loss and glial proliferation. NKCC1 blockage confirmed that the NKCC1 increase contributed to NEA changes in DG. Abstract: Understanding the mechanisms that influence brain excitability and synchronization provides hope that epileptic seizures can be controlled. In this scenario, non-synaptic mechanisms have a critical role in seizure activity. The contribution of ion transporters to the regulation of seizure-like activity has not been extensively studied. Here, we examined how non-synaptic epileptiform activity (NEA) in the CA1 and dentate gyrus (DG) regions of the hippocampal formation were affected by kainic acid (KA) administration. NEA enhancement in the DG and suppression in area CA1 were associated with increased NKCC1 expression in neurons and severe neuronal loss accompanied by marked glial proliferation, respectively. Twenty-four hours after KA, the DG exhibited intense microglial activation that was associated with reduced cell density in the infra-pyramidal lamina; however, cellular density recovered 7 days after KA. Intense Ki67 immunoreactivity was observed in the subgranular proliferative zone of the DG, which indicates new neuron incorporation into the granule layer. In addition, bumetanide, a selective inhibitor of neuronal Cl − uptake mediated by NKCC1, was used to confirm that the NKCC1 increase effectively contributed to NEA changes in the DG. Furthermore, 7 days after KA, prominent NKCC1 staining was identified in the axon initial segments of granule cells, at the exact site where action potentials are preferentially initiated, which endowed these neurons with increased excitability. Taken together, our data suggest a key role of NKCC1 in NEA in the DG.